DIGITAL LITERACY IN THE PROCESS OF TEACHING IN LEARNING LESSONS OF PHYSICAL EDUCATION (Fiep Bulletin - online, 2016)
The use of digital literacy in the teaching / learning process is aimed at the inclusion of new teaching procedures in physical education classes, hoping to arouse greater participation and interest in the practice. Digital tools bring us lots of information. Young people are embedded in these technologies from an early age, and in this context it is important that these tools are used to provide knowledge, not only for entertainment and social interaction. The aim of this study using a new approach to teaching in the classroom in order to bring about greater interest in the practice. This research was conducted with 59 students, of both genders, attending the 9th grade at a school in the municipal Joinville - SC. The intervention in the classes occurred with plans that relate theoretical and practical classes with the help of tablets in the execution of activities. At the end of the activities were reports prepared by students on the relationship observed between theoretical classes with the help of tablets and practical classes. Analyzing the contents of the reports submitted by students, stood out three (3) categories of analysis: interaction of technology in teaching generating new learning; methodological innovation and motivation. From the reports it was observed that the insertion of the digital tool enabled students greater understanding of the rules as well as felt more willing and interested to carry out the activities.
Keywords: digital literacy; education / learning; physical education.